Nietzsche-figura, Nietzsche-concetto, Nietzsche-azione. Il triplice valore di Nietzsche nella prima ricezione italiana - Pardi, Aldo (Filosofia, 2017)
The paper retraces the Italian reception of Nietzsche at the end of XIX century. The aim of the paper is to present the history of first readings of Nietzsche in Italy and to show their complex articulation. The author argues that Nietzsche’s works were promptly received in aesthetic and artistic milieus, especially by the Scapigliatura movement. At the same time, Nietzsche’s images and categories were assumed and discussed by many of the principal anarchist Italian intellectuals, which were in close relationship with Scapigliati artists and writers. In the paper, the author reconstructs this economy of cultural exchanges. The “figure” of Nietzsche as an “object” and “measure” of cultural value is reconstructed through a bibliographic analysis particularly focused on artistic, political and philosophical subversive experiences.